Characteristics of Helicobacter pylori infection in a private hospital in Lima, 2019 experience and literature review - Yoza Yoshidaira, Max (2022)
Digestive diseases are the fourth leading cause of outpatient care in Peruvian healthcare centers, with gastritis and peptic ulcers being the most common. This is a retrospective, cross-sectional, descriptive study of secondary analysis of medical record data to evaluate the prevalence of Helicobacter pylori in patients undergoing upper digestive endoscopy during 2019 at Clinica Delgado, Lima, Peru. An association between males (PRa 1.27, 95% CI 1.10-1.48, p<0.001), age categories and upper digestive endoscopy (PRa 2.53, 95% CI 2.16-2.97, p<0.001) was reported. Based on these findings, it is recommended that other causes of gastritis be identified, especially in young women with deep chronic gastritis. Furthermore, we present a review of the scientific literature of Peru on factors associated with the positivity of Helicobacter pylori in the results of superior digestive endoscopy.